2014
DOI: 10.1159/000357015
|View full text |Cite
|
Sign up to set email alerts
|

Combined Extracorporeal Therapy for Severe Sepsis in Patients after Cardiac Surgery

Abstract: Introduction: Sepsis still represents an obstacle in modern medicine. The aim of this study was to evaluate the effectiveness and safety of the combined use of lipopolysaccharide adsorption and haemodialysis (HD) with high cut-off haemofilters as part of the complex intensive care of patients with severe sepsis after cardiac surgery. Methods: The study group included 26 patients, 57 (48-62) years of age, with severe sepsis. The inclusion criteria were clinical signs of severe sepsis (systemic inflammatory resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
16
0
4
Order By: Relevance
“…Bakulev NSPCCS in 2009-2016, showed the safety and efficacy of the combined therapies mentioned above. [53,54] We observed that the combination of LPS-adsorption and HDF filters with high cut-off EMiC2 membranes led to a 34% MAP increase [from 76 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) to 90 (85-102) mmHg, P < 0.001] with reduced vasopressor and inotropic support. The increase in MAP during LPS-adsorption with CPFA was 12% with the significant decrease in vasopressor support [the dose of noradrenaline was halved from 0.2 (0.15-0.3) to 0.1 (0.05-0.15) µg/kg/min, P = 0.024].…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 89%
See 3 more Smart Citations
“…Bakulev NSPCCS in 2009-2016, showed the safety and efficacy of the combined therapies mentioned above. [53,54] We observed that the combination of LPS-adsorption and HDF filters with high cut-off EMiC2 membranes led to a 34% MAP increase [from 76 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) to 90 (85-102) mmHg, P < 0.001] with reduced vasopressor and inotropic support. The increase in MAP during LPS-adsorption with CPFA was 12% with the significant decrease in vasopressor support [the dose of noradrenaline was halved from 0.2 (0.15-0.3) to 0.1 (0.05-0.15) µg/kg/min, P = 0.024].…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 89%
“…[47,51,52] Modern methods of blood purification allow etiopathogenic therapy application for sepsis: to eliminate the etiotropic agent (endotoxin) by selective lipopolysaccharide (LPS)-adsorption and to remove the effector substances of systemic inflammation, replacing the functions of the affected organs and recovering the body's homeostasis by coupled plasmofiltration and adsorption (CPFA), convection and filtration techniques using ultrahigh permeable membranes. [53,54] Many authors have observed that LPS-adsorption with PMX cartridges leads to a significant decrease in endotoxin activity levels after two consecutive procedures. [55] Positive dynamics of the endotoxin concentration (lowering by 38%) in patients with abdominal sepsis and septic shock were demonstrated in the European multicenter study "EUPHAS".…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 99%
See 2 more Smart Citations
“…I read with great interest the article published in your journal by Yaroustovsky et al [1] regarding the beneficial effects of combining hemodialysis with high cutoff membranes (continuous venovenous hemodiafiltration with high cutoff membranes, HCO-CVVHD) and lipopolysaccharide adsorption in cardiac surgery patients with severe sepsis. The authors reported that the benefits of using extracorporeal therapies were demonstrated by several changes in the parameters analyzed, including the reduction of procalcitonin (PCT) during treatment.…”
mentioning
confidence: 99%